Analysis of rainbow trout TCRαβ/CD3 complex: An in-silico modeling approach. (April 2022) - Flores-Kossack, C.; Muñoz, C.; Fuentes, N.; Maisey, K.
Abstract: In mammals, the T lymphocyte receptor (TCR) is a multiprotein complex formed by the proteins TCRα, TCRβ, CD3ε, CD3γ, CD3δ, and CD3ζ. It is responsible for recognizing antigens processed and presented by antigen-presenting cells (APC). The TCR is located at the cytoplasmic membrane of the T lymphocyte but is functional assembled in the rough endoplasmic reticulum (RER). Most of the available information on TCR constituents in salmonids comes from numerous nucleotide sequences available in different databases. In this work, by in silico homology modeling, we generated the TCRαβ/CD3 complex of rainbow trout ( Oncorhynchus mykiss ) and characterized the structure of the different proteins and their potential interactions. The results show that the main structural features described in mammalian TCR/CD3 are present in the model predicted for trout. Furthermore, we highlighted several aminoacidic interactions between TCRα, TCRβ, CD3γδ, and CD3ε. In silico structural analyses suggest that trout TCRαβ complex would fit similarly to that described for mammals. Herein, we explore the implications of the modeled trout complex and the leukocyte phenotypes, mainly associated with different regulation mechanisms of trout TCRαβ/CD3 subunits gene expression or may be due to differences in the assembly process of the complex in the RER. However, further studies will be needed to study deeper the mechanisms involved. Highlights: In-silico model of trout TCRαβ/CD3 complex is homologous to the human TCR complex. Trout TCRαβ-CD3 subunits contain peculiar structural elements that would impact the formation of the complex. Modeling would support understanding the evolutionary relationship among mammalian and trout TCRαβ/CD3 components.